Work motivation and work environment in improving employee performance at PT Telkom Witel Banten Persero - Triana Perry; Syaechurodji Syaechurodji; Didit Haryadi (Trigin Publisher, 2023)
Among effective management systems, the importance of human resources is increasing. Employee performance is an essential factor that influences success. In an organization, this is one of the most critical functions of an institution. This research aims to determine the variables influencing employee performance and develop a theoretical basis and research model. This research used an associative descriptive quantitative method with a population of 58 respondents who were drawn into the sample using non-probability sampling, using a saturated/total sampling method. The data analysis technique uses linear regression with the help of SPSS version 26 software. The results of this research show that the first hypothesis states that employee performance is influenced by work motivation, meaning that the higher the work motivation an employee has, the higher the employee's performance. Thus, the second hypothesis states that employee performance is influenced by the work environment, meaning that the better the work environment, the more employee performance will increase. The third hypothesis is that employee performance is influenced by work motivation and work environment, which can simultaneously improve employee performance. This research is expected to provide a theoretical contribution to the literature in this context, of course, in the context of human resource management.